Chemisorption and the Distribution of Acid Y Zeolite Cumene Cracking Products - Lyubov Patrylak (Adsorption Science & Technology)
The results obtained for the pulse cracking of cumene in the presence of zeolite-containing acidic catalysts were analyzed taking into account data complications arising because of the chemisorption of the components of the reaction mixture on the acid sites of the catalyst samples. The propene/benzene (P/B) molar ratios in the reaction mixtures, which amounted to 0.60–2.7, deviated considerably from the expected stoichiometry depending on the nature of the samples, their mode of preparation, their preliminary thermal treatment and steaming as well as on the experimental conditions employed. At the same time, the total yields of cracking products and non-converted cumene were, as a rule, 1.5–3-times less than the amounts of cumene fed into the system. The infringement of the stoichiometry and the considerable material imbalance observed may be attributed to the chemisorption of both cumene and the final conversion products on Lewis acid sites, i.e. coordinatively unsaturated aluminium atoms and zeolite cations, present on the catalyst surface. Chemisorption of the intermediates — phenyl carbocations — on Brönsted acid sites, as well as coke formation as a result of propene polymerization on these sites, must also be taken into consideration. The balance between these various processes and interactions leads to the overall reaction situation observed, thereby enabling conclusions to be drawn regarding both the nature of the catalyst surface and the individual processes, which appear to depend on the strength, amount and correlation between the Brönsted and Lewis acid sites on the samples studied.